Elevated CPW-Fed Slotted Microstrip Antenna for Ultra-Wideband Application. (5th November 2012) - Ghosh, Chandan Kumar; Roy, Arabinda; Parui, Susanta Kumar
Abstract : Elevated-coplanar-waveguide- (ECPW-) fed microstrip antenna with inverted "G" slots in the back conductor is presented. It is modeled and analyzed for the application of multiple frequency bands. The changes in radiation and the transmission characteristics are investigated by the introduction of the slots in two different positions at the ground plane (back conductor). The proposed antenna without slots exhibits a stop band from 2.55 GHz to 4.25 GHz while introducing two slots on the back conductor, two adjacent poles appear at central frequencies of 3.0 GHz and 3.9 GHz, respectively, and the antenna shows the ultra-wideband (UWB) characteristics. The first pole appears at the central frequency of 3.0 GHz and covers the band width of 950 MHz, and the second pole exists at a central frequency of 3.90 GHz covering a bandwidth of 750 MHz. Experimental result shows that impedance bandwidth of 129% (S11 < - 10  dB) is well achieved when the antenna is excited with both slots. Compared to most of the previously reported ECPW structures, the impedance bandwidth of this antenna is increased and also the size of the antenna becomes smaller and more suitable for many wireless applications like PCS (1850–1990 MHz), WLAN (2.4–2.484 GHz), WiMAX (2.5–2.69 GHz and 5.15–5.85 GHz), and also X-band communication.